Development and characterization of microsatellite loci for common raven (Corvus corax) and cross species amplification in other Corvidae. (December 2015) - Pruett, Christin; Wan, Leping; Li, Tianyu; Spern, Cory; Lance, Stacey; Glenn, Travis; Faircloth, Brant; Winker, Kevin
Abstract Background A priority for conservation is the identification of endemic populations. We developed microsatellite markers for common raven (Corvus corax ), a bird species with a Holarctic distribution, to identify and assess endemic populations in Alaska. Results From a total of 50 microsatellite loci, we isolated and characterized 15 loci. Eight of these loci were polymorphic and readily scoreable. Eighteen to 20 common ravens from Fairbanks, Alaska were genotyped showing the following variability: 3–8 alleles per locus, 0.25–0.80 observed heterozygosity (Ho ), and 0.30–0.80 expected heterozygosity (He ). All loci were in Hardy–Weinberg equilibrium and linkage equilibrium and many loci amplified and were polymorphic in related taxa. Conclusions These loci will be used to identify endemic populations of common raven and assess their genetic diversity and connectivity.